2016
DOI: 10.1097/hjh.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin receptor contributes to regulation of renal epithelial sodium channel

Abstract: Recent studies reported increased (Pro)renin receptor (PRR) expression during low-salt intake. We hypothesized that PRR plays a role in regulation of renal epithelial sodium channel (ENaC) through serum and glucocorticoid-inducible kinase isoform 1 (SGK-1)-neural precursor cell expressed, developmentally downregulated 4–2 (Nedd4–2) signaling pathway. Male Sprague–Dawley rats on normal-sodium diet and mouse renal inner medullary collecting duct cells treated with NaCl at 130 mmol/l (normal salt), or 63 mmol/l (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 35 publications
7
28
0
Order By: Relevance
“…Moreover, the other ENaC subunits (β & γ) remain unchanged. In agreement with our results, Quadri et al showed that in vivo delivery of shRNA against PRR to the kidney of Sprague-Dawley rats selectively reduced α-ENaC expression in the renal medulla but not in the cortex despite the gene knockdown in the whole kidney 33 . These results suggest that PRR may primarily target renal medullary (or inner medullary) ENaC to regulate Na + balance and BP.…”
Section: Prr Regulation Of Na+ Homeostasissupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the other ENaC subunits (β & γ) remain unchanged. In agreement with our results, Quadri et al showed that in vivo delivery of shRNA against PRR to the kidney of Sprague-Dawley rats selectively reduced α-ENaC expression in the renal medulla but not in the cortex despite the gene knockdown in the whole kidney 33 . These results suggest that PRR may primarily target renal medullary (or inner medullary) ENaC to regulate Na + balance and BP.…”
Section: Prr Regulation Of Na+ Homeostasissupporting
confidence: 93%
“…Besides the above-mentioned in vitro data, strong in vivo data from 3 independent studies all support an important role of PRR in ENaC regulation under basal and/or pathophysiological conditions 29, 32, 33 . To our surprise, PRR regulation of ENaC appears to occur only in the renal medulla but not the cortex.…”
Section: Prr Regulation Of Na+ Homeostasismentioning
confidence: 79%
See 1 more Smart Citation
“…17 Recent studies also demonstrate that PRR in renal tubular epithelia regulates BP and sodium transport. 18,19 Taken together, these investigations establish a critical role for PRR in regulating normal kidney development, tissue hemostasis, and BP regulation.…”
mentioning
confidence: 81%
“…In the kidney, the PRR is mainly expressed in cells of the collecting ducts and in the distal nephron (Advani, et al, 2009), where it may complex with vacuolar H + -ATPase to regulate proton transport (Advani, et al, 2009; Daryadel, et al, 2016). Expression of the PRR is regulated by changes in sodium concentration induced by the cGMP-dependent protein kinase (PKG) pathway in the kidney (Huang & Siragy, 2011; Quadri & Siragy, 2016; Rong, et al, 2015). In addition, PRR expression levels are regulated by Ang II through CREB (cAMP response element binding protein) in the central nervous system (CNS) during hypertension (W.…”
Section: Introductionmentioning
confidence: 99%